Molecular docking tutorial using AutoDock 4.2.6 on SARS-CoV-2 main protease for beginner - Quan, Pham Minh; Huong, Le Thi Thuy; Minh, Pham Thi Hong; Toan, Tran Quoc; Lam, Do Tien; Le, Vu Thi Thu; Long, Pham Quoc (Vietnam Journal of Science and Technology, 2022)
The worldwide pandemic caused by coronavirus SARS-CoV-2 (so called as COVID-19 disease) has affected 219 countries and territories, leading to numerous deaths and global financial crisis. The main protease (Mpro) of SARS-CoV-2 plays an important role in mediating the transcription and replication of virus, thus, one of the main therapeutic is to find compounds that are capable of inhibiting these enzymes as soon as possible. Nowadays, computer-aided drug design plays an important role in the field of drug discovery. In particular, molecular docking is one of the initial steps that effectively screen numerous number of compounds for their interaction and binding affinity toward targeted enzyme, therefrom, suggesting a short list of potential inhibitors for further drug development processes. As part of our ongoing program to provide simple guideline for scientific community to utilize different docking tools for research purposes. In this article, a complete manual guideline of Autodock 4.2.6 is presented to demonstrate the simulation of interaction between PF-07321332 compound and the main protease of SARS-CoV-2, thus, suggest an effective tool for scientists to conduct reseach on this disease.